The Effect of Management Capability on the Performance of Sasirangan Small and Medium Industry (SME) in South Kalimantan Province - Maskur Maskur (Wacana Journal of Social and Humanity Studies, 2017)
The economic crisis that occurred in Indonesia since some time ago, whereas many large-scale businesses get stagnated and even its activity stopped. The Small and Medium Industry (SME) sector proved to be more resilient in facing the crisis. Given the experience that Indonesia has faced during the crisis, it is not excessive if private sector development is focused on SME. SME is placed in a factual position because SME is considered to accomplish the necessity to diversify national economy in order to protect it against economic fluctuation and crescents. Management capability is very significant in small, medium and large industries, where each requires management activities to coordinate the skills or the workers’ skills and the resources coordination owned by the company. The purpose of this study is to examine and explain the effect of management capability on the performance of Sasirangan Small and Medium Industry (SME) in South Kalimantan Province. The method used is a quantitative approach (positivism), because the obtained data from the survey results are in the form of numbers or digits which then analyzed using statistics to answer questions and test the research hypothesis. The result of the research shows that management capability has a significant direct positive effect on SME performance. GeSCA results obtained by path coefficient of 0.029* and CR = 4.28* (significant) are positive. This result indicates that management capability owned by SME Sasirangan owner can improve SME performance.Keyword: Management, Small and Medium Industry (SME)